Bierny udział w biegowych wydarzeniach sportowych i jego wpływ na promocję zdrowia i aktywności fizycznej wśród kibiców = Passive participation in cross-country running sporting events and their impact on health promotion and physical activity among fans - Poczta, Joanna; Malchrowicz-Mośko, Ewa (Journal of Education, Health and Sport, 2016)
Poczta Joanna, Malchrowicz-Mośko Ewa. Bierny udział w biegowych wydarzeniach sportowych i jego wpływ na promocję zdrowia i aktywności fizycznej wśród kibiców = Passive participation in cross-country running sporting events and their impact on health promotion and physical activity among fans. Journal of Education, Health and Sport. 2016;6(1):107-117. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.44751 http://ojs.ukw.edu.pl/index.php/johs/article/view/44751 http://pbn.nauka.gov.pl/works/694607 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.12.2015. Revised 25.12.2015. Accepted: 09.01.2016. Bierny udział w biegowych wydarzeniach sportowych i jego wpływ na promocję zdrowia i aktywności fizycznej wśród kibiców Passive participation in cross-country running sporting events and their impact on health promotion and physical activity among fans Joanna Poczta, Ewa Malchrowicz-Mośko Zakład Kulturowych Podstaw Turystyki, Wydział Turystyki i Rekreacji, Akademia Wychowania Fizycznego im. E. Piaseckiego w Poznaniu Department of Cultural Foundations of Tourism Tourism and Recreation Faculty University School of Physical Education in Poznan Streszczenie Popularyzacja biegania jako ogólnodostępnej i taniej formy aktywności fizycznej jest bardzo duża, zarówno w Polsce jak i na Świecie. W masowych wydarzeniach biegowych bierze udział coraz więcej osób biegających oraz kibicujących. Celem artykułu jest wykazanie, czy i w jakim stopniu bierny udział w wydarzeniach biegowych wpływa na postawy wobec aktywności fizycznej. Postanowiono sprawdzić w tym zakresie deklaracje kibiców 6. Poznań Półmaratonu i określić – po pierwsze - czy uczestnictwo w imprezie w charakterze kibica motywuje do podejmowania aktywności fizycznej oraz - po drugie - czy wpływa na decyzję o wzięciu czynnego udziału w tej lub innej tego typu imprezie w przyszłości jako zawodnik, co ściśle wiąże się z systematyczną, przemyślaną aktywnością fizyczną i zmianą stylu życia podporządkowanego przygotowaniom do startu w imprezie. Prezentowany materiał stanowią badania przeprowadzone w trakcie trwania 6. Poznań Półmaratonu w dniu 7 kwietnia 2013 roku na terenie miasta Poznania na trasie biegu. Słowa kluczowe: biegowe wydarzenia sportowe, promocja zdrowia, aktywność fizyczna. Abstract Popularization of running as accessible and cheap form of physical activity is very high, both in Poland and in the world. The mass cross-country events involved more and more people running and cheering. This article aims to show whether and how passive participation in cross-country events affect attitudes toward physical activity. It was decided to check in this regard declarations of fans 6. Half-marathon Poznan and identify - first - whether to participate in the event as a fan motivates physical activity and - secondly - whether it affects the decision to take an active part in this or any other similar event in the future as a player, which is closely associated with systematic, well thought physical activity and lifestyle change subordinated preparations to take part in the event. The material presented is in the study carried out during the sixth Poznan Half Marathon on 7 April 2013 in the city of Poznan along the route. Key words: cross-country sport events, running sport events, health promotion, physical activity.